Manual on the use of timber in coastal and river engineering - Crossman, Matt; Simm, Jonathan (Thomas Telford, 2004)
Designed to provide guidance on the principal issues surrounding the use of timber in coastal and river engineering. This manual provides an introduction to the use and properties of timber, a framework for responsible selection and procurement of timber materials, discussion of design and construction issues and maintenance practices, and more.